The acute effects of dynamic vs static stretching on vertical jump in female athletes - Millikan, A.; Gutierrez, D.; Grabner, A.; Miller III, F. L. (International Journal of Research in Exercise Physiology, 2015)
Introduction: This study aimed to determine which type of stretching technique used during a warm-up was appropriate before power exercise in female athletes. The effects of static stretching and dynamic stretching were compared using explosive force production during a vertical jump exercise. Methods: Participants (N = 40) were all DIII female athletes between the ages of 18-22 years of age. Participants completed three separate experimental sessions with a full 48 hours in between each session. The first session participants were asked to self-pace jog 400m before completing three consecutive vertical jumps with a counter movement. The best of the three jumps were recorded. The second session the participants were asked to self-pace jog the same 400m distance, but perform a static stretching routine focusing on necessary muscles to perform the vertical jump. After static stretching, participants performed three consecutive vertical jumps with the best jump recorded. The third and final session, participants jogged a self-paced 400m distance and performed a dynamic stretching routine that focused on muscles important to vertical jump. After dynamic stretching, participants performed three consecutive vertical jumps with the best jump recorded. Results: Mean vertical jump performance following control, static, and dynamic conditions were 18.6 ± 2.1 in, 18.6 ± 2.1 in, and 19.5 ± 2.0 in, respectively. Vertical jump was significantly greater (p < 0.05) following a dynamic warmup when compared to static stretching or control conditions. Conclusions: Our findings support use of a dynamic warmup to improve vertical jump performance in an athletic population.